치과위생사의 전문직업적 정체성과 관련 요인 - 박정은; Jung-eun Park; 김설악; Seol-ak Kim; 박용덕; Yong-duk Park (Han'guk Ch'iwisaeng Hakhoe chi, 2016)
Objectives: The purpose of the study was to investigate the professionalism identity and related factors in dental hygienists. Methods: A self-reported questionnaire was completed by 347 dental hyfienists from March 5 to May 31, 2015. Except incomplete 39 answers, data were analyzed by frequency analysis, ANOVA, Pearson``s correlation coefficient, and multiple regression analysis using SPSS 22.0. The questionnaire comprised 25 items including professionalism scale by Hall, Snizek, and Anderson by Likert 5 point scale. Results: Professionalism scale revealed self-regulation(3.65±0.58), service conviction(3.64±0.62), skills and training(3.21±0.70), sense of professional vocation(3.20±0.65), and thought about professional group(3.08±0.78). The professionalism identity by general characteristics showed significant differences and there were positive correlations in main factors. The identity level was influenced by internal factors rather than economic compensation. Conclusions: There were positive correlation in main factors. The identity level was influenced by internal factors.